2016
DOI: 10.1038/onc.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

A novel nickel complex works as a proteasomal deubiquitinase inhibitor for cancer therapy

Abstract: Based on the central role of the ubiquitin–proteasome system (UPS) in the degradation of cellular proteins, proteasome inhibition has been considered an attractive approach for anticancer therapy. Deubiquitinases (DUBs) remove ubiquitin conjugates from diverse substrates; therefore, they are essential regulators of the UPS. DUB inhibitors, especially the inhibitors of proteasomal DUBs are becoming a research hotspot in targeted cancer therapy. Previous studies have shown that metal complexes, such as copper an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 46 publications
5
61
0
Order By: Relevance
“…Like in other cancer cells, we previously reported [27], we found that NiPT dose- and time-dependently induced accumulation of ubiquitinated proteins (Ubs) and proteasome substrate protein p27 in all CML cell lines we detected before the emergence of PARP cleavage (Fig. 3a).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Like in other cancer cells, we previously reported [27], we found that NiPT dose- and time-dependently induced accumulation of ubiquitinated proteins (Ubs) and proteasome substrate protein p27 in all CML cell lines we detected before the emergence of PARP cleavage (Fig. 3a).…”
Section: Resultssupporting
confidence: 77%
“…As displayed in Fig. 5a, NiPT decreased the cell viability of primary monocytes from CML patients with IC 50 values ranging from 0.58 to 0.82 μM, while for the peripheral mononuclear cells from three healthy volunteers the IC 50 values were more than 3.0 μM as we reported recently [27].
Fig.
…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations